Caregivers' voices; attitudes towards elderly and care giving [Bakicilarin sesi̇; yaşlilar ve bakicilik hakkindaki̇algi ve tutumlari] - (:unkn) unknown (My University, 2009)
Introduction: Although elderly care needs specific approah, generally by family given members or informal care-givers. In this study, we aimed to define these care givers' thoughts, perceptions, attitudes, emotions and problems with the care giving and the elderly. Materials and Method: In this qualitative research, an interviewer and an observer conducted two structured focus group interviews with 10 participants. Interviews were taped and transcribed verbatim. Two researchers independently analyzed and coded the transcripts, then compromised on and listed the codes. Similar codes are grouped under same themes. Results: Expressions were grouped under 5 main themes; reasons to start that job, qualifications of care-givers and job content, the care-givers' emotions, occupational difficulties and the points that they need support. Economic income was the reason to choose the job. The caregivers defined their job both under terms of health care and daily care. They were satisfied when they fulfilled their responsibilities. The most important difficulty was to be dependent on the person who they took care. Primary needs were education, psychological and physical support. Conclusion: Traditional care of elderly by family members might be an important and easier profession if it is supported by training. Care-givers' health maintenance and needs must be provided and new strategies must be developed.
Keywords: Care; Care-giver; Elderly health; Geriatrics; Needs; Qualitative